An evolutionary approach to adaptive capacity assessment: A case study of Whitehouse, Jamaica - Hogarth, JR; Wojcik, D (Elsevier, 2016)
This paper assesses the capacity of Whitehouse, Jamaica to adapt to climate change. A community-based vulnerability assessment was conducted that employed semi-structured interviews with community members within or related to the tourism, fisheries and agricultural sectors. The results were analysed using the Local Adaptive Capacity (LAC) framework, which characterises adaptive capacity based on five elements: asset base; institutions and entitlements; knowledge and information; innovation; and flexible forward-looking decision-making and governance. This paper contributes to the literature in three ways. First, it argues that many elements of the LAC framework correspond with an evolutionary perspective on adaptive capacity. Second, it offers an in-depth case study of the capacity of Whitehouse to adapt to climate change. Third, it offers a critical assessment of whether the LAC framework fully captures the important elements of adaptive capacity.